2019
DOI: 10.1002/ece3.5741
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for early fitness penalty in glyphosate‐resistant biotypes of Conyza canadensis: Common garden experiments in the absence of glyphosate

Abstract: Strong selection from herbicides has led to the rapid evolution of herbicide‐resistant weeds, greatly complicating weed management efforts worldwide. In particular, overreliance on glyphosate, the active ingredient in RoundUp®, has spurred the evolution of resistance to this herbicide in ≥40 species. Previously, we reported that Conyza canadensis (horseweed) has evolved extreme resistance to glyphosate, surviving at 40× the original 1× effective dosage. Here, we tested for underlying fitness effects of glyphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…These results are consistent with those observed by Costa et al [23] in C. bonariensis. At the vegetative level, there is no evidence for fitness cost in glyphosate-resistant Conyza species [5,26,28,37]; however, our results suggest that there may be a seed level fitness penalty in C. bonariensis. Piasecki et al [18] also observed a reduction in the vigor and germination rate in seeds of glyphosate-resistant Conyza species and, in turn, a significant increase in both empty and dormant seeds.…”
Section: Discussionmentioning
confidence: 54%
“…These results are consistent with those observed by Costa et al [23] in C. bonariensis. At the vegetative level, there is no evidence for fitness cost in glyphosate-resistant Conyza species [5,26,28,37]; however, our results suggest that there may be a seed level fitness penalty in C. bonariensis. Piasecki et al [18] also observed a reduction in the vigor and germination rate in seeds of glyphosate-resistant Conyza species and, in turn, a significant increase in both empty and dormant seeds.…”
Section: Discussionmentioning
confidence: 54%
“…al. 2008, Vila-aiub et al 2015).In the absence of the selective pressure, if an herbicide resistance does not confer a tness cost or if it is associated with a tness bene t (Beres, Yang, et al 2018;Wang et al 2014), this trait has the potential to persist in the environment inde nitely(Beres, et al 2019). Fitness cost will depend on factorslike the speci c mutation that gives herbicide resistance (Vila-Aiub et al 2009; Yu et al 2010; Ashight et al 2007; Purrington et al 1999, Menchari et al…”
mentioning
confidence: 99%